21 Bar Yoshimin Boiler Maintenance with Controlling Residual Phosphate - Agung Subyakto; Afan Hamzah; Agus Surono (Institut Teknologi Sepuluh Nopember, 2020)
Boiler as the steam generator is usually utilized as a turbine drive and other industrial processes. Boiler needs good treatment and surveillance to keep its best performance. Boiler water (BW) and boiler feed water (BFW) quality control is essential in boiler maintenance since it preserves boiler from crust, corrosion, and carry over, moreover, it also prevents boiler pipe to break. Boiler maintenance in sugar refinery factory is carried out by controlling the quality of BFW, Chemical injection (inner maintenance) and blowdown of boiler water. BFW mineral content (SiO2 , total hardness) is maintained as small as possible using a softener (cation resin) or demineralization unit (cation and anion resin). Chemical injection is performed by the addition of soda in order to control the pH of boiler water. Phosphate addition aims to tie up total hardness level which is caused by concentration process of water boiler and slipped of hard water from BFW. Blowdown process has purpose to reduce crust and corrosion caused by mineral concentrate inside boiler. The experiment was conducted by controlling pH of BFW from 7.5-8.5, maximum total hardness at 3 ppm, maximum SiO2 concentration at 3 ppm and maximum Total Dissolve Solid (TDS) at 100 ppm while BW was controlled its pH at 10.5-11, maximum total hardness at 20 ppm, maximum SiO2 concentration at 50 ppm, maximum Total Dissolve Solid (TDS) at 2000 ppm, and residual phosphate ion between 4 – 10 ppm. The experiment time was adjusted as a milled day or about for 140 days. The result of the experiment showed that the treatment had a good impact on the condition of the boiler drum pipe.